Manajemen Strategi Pemasaran Bisnis dalam Era Globalisasi Mobil Honda di Industri Otomotif - Rizky Jaya Capriyansyah; Rizki Mulya Ardana; Mohamad Zein Saleh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In today's era, business competition is getting tighter, including among similar business players in the Asian free market. Competition is not only about price and product quality, but also includes marketing strategies, service innovation, and maintaining consumer loyalty. This research aims to analyze the marketing strategies implemented by PT. Honda Prospect Motor (HPM) in facing globalization and the Asian free market through a SWOT analysis approach. In the context of increasingly tight competition in the motorcycle market, HPM must be able to adapt effective marketing strategies to maintain its position as the market leader in Indonesia and develop its market share in Asia. This research uses a qualitative approach with a case study on HPM, exploring the strengths, weaknesses, opportunities, and threats faced by the company in the context of a free market and the dynamics of the automotive industry. The analysis results show that HPM has strengths in a strong brand, extensive distribution networks, and innovation capabilities in products. However, there are weaknesses in product diversification and dependence on the domestic market. Existing opportunities include market expansion in Asia and increasing demand for environmentally friendly vehicles, while threats come from intense competition and fluctuations in the global economy. Based on these findings, HPM is expected to develop more adaptive and globalization-oriented marketing strategies to enhance competitiveness in the Asian market.